High-quality silicon nitride ceramic powders by direct nitriding method - ZHAO Liyan; LIU Yaoyao; YANG Jingsi; HAN Jiangze; LI Kunjie; ZHAO Ruihong; ZHAO Jiasai (Fenmo yejin jishu)
High-quality silicon nitride ceramic powders were prepared by direct nitriding method with silicon powders as the raw materials. The effects of nitriding temperature, heating rate, particle size of silicon powders, and dosage of diluent on the silicon nitride ceramic powders were studied. In the results, when the reaction temperature is 1400 ℃ and the heating rate is controlled at 5 ℃·min−1 during 1100~1400 ℃, the raw silicon powders without the Si3N4 diluent are completely nitrided, the spherical silicon nitride materials with the uniform particle size (396～458 nm) and good dispersion are prepared, and the mass fraction of the α phase is 95.02%. The results show that, with the increase of nitriding temperature, the direct nitriding reaction of silicon powders shows an obvious stage. At the same reaction time, the best nitriding temperature is 1400 ℃, too high or too low reaction temperature could affect the competitive relationship between the transition from α-Si3N4 to β-Si3N4 at the silicon powder interface and the internal nitriding reaction, affecting the content of α-Si3N4. The heating rate is the key factor to control the reaction process, and the optimal heating rate is 5 ℃·min−1. When the heating rate is too fast or too slow, the transformation degree of silicon nitride from α phase to β phase exceeds the internal reaction degree, and the silicon powder reaction is incomplete. The suitable milling time can reduce the particle size of raw silicon powders, increase the specific surface area, and increase the contact area between silicon powders and nitrogen, which can improve the nitriding rate and increase the mass fraction of α-Si3N4. The addition of α-Si3N4 diluent can reduce the oxygen content and nitriding temperature of silicon powders, accelerate the nitriding process, and promote the formation of α-Si3N4 in the product. It can also absorb the additional heat released by the reaction between silicon and nitrogen, and mainly plays the role of heating body in the direct nitriding reaction of silicon powders.